Szkołownia as a cultural conceptualization of Summer Schools of Young Pedagogues - Mariusz Dembiński (Studia z Teorii Wychowania)
The essence of this statement is the attempt to demonstrate, that Summer Schools of Young Pedagogues in his own (original) form, implemented by Maria Dudzikowa, were ukształcającym (Bildung) phenomenon pedagogical, and at the same, a polyphonic cultural occurrence. As a pedagogical phenomenon, played a unifying and holistic role in shaping the pedagogical thought developed in Poland since 1993. As a cultural occurrence, they became executive (performative) spectacles of pedagogical reality, which I bring to the notion of Szkołownia - polyphonic form of performative genres of cultural executive, constituting a conceptual foundation for liminal changes of consciousness of individuals, as well as pedagogy itself.